PARADOKS DIGITALISASI PELAYANAN PUBLIK: STUDI KESENJANGAN DESAIN-REALITAS DAN PERSISTENSI BIROKRASI MANUAL DALAM IMPLEMENTASI M-PASPOR - Nur Muhammad Alil Makmur S; Herman H; Muhammad Irvan Nur I’va; Rahayu Rahayu; Andi Asrifan (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2026)
Digital transformation is not simply a conversion from manual to electronic, but rather a fundamental shift in how organizations create public value. In the context of M-Passport, system failures are often caused not by programming weaknesses alone, but by the unpreparedness of the surrounding ecosystem. Data shows that despite the application's launch in January 2022, many Technical Implementation Units (UPTs), such as in Makassar, still implement hybrid practices where physical documents remain the